Segregation of alloying elements to intrinsic and extrinsic stacking faults in γ′-Ni3Al via first principles calculations. (June 2015) - Eurich, N.C.; Bristowe, P.D.
Abstract : First principles calculations are used to investigate the segregation behaviour of Co, Cr, Re, Mo and W to intrinsic and extrinsic stacking faults in γ′-Ni3 Al. It is shown that the change in stacking fault energy depends on local alloying concentration and is related to subtle changes in the electronic structure of the alloying elements and adjacent nickel atoms. The results are consistent with observed stacking fault segregation in commercial superalloys and in particular the behaviour of Co and Cr.